Certain sufficient conditions for parabolic starlike and uniformly close-to-convex functions - BRAR, Richa; BILLING, Sukhwinder Singh (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
In the present paper, we study certain differential subordinations and obtain sufficient conditions for parabolic starlikeness and uniformly close-toconvexity of analytic functions. Mathematics Subject Classification (2010): 30C80, 30C45.